Rate of Union After Segmental Midshaft Shortening Osteotomy of the Lesser Metatarsals. (October 2015) - DeSandis, Bridget; Ellis, Scott J.; Levitsky, Matthew; O'Malley, Quinn; Konin, Gabrielle; O'Malley, Martin J.
Background: Current literature reports excellent rates of union following various lesser metatarsal osteotomy techniques. However, it is our experience that segmental midshaft shortening osteotomies heal very slowly and have a greater potential for nonunion than has previously been reported. The purpose of this study was to assess union rates and report the time required for segmental midshaft shortening osteotomies to achieve radiographic union. Methods: We reviewed the charts and postoperative radiographs of 58 patients (representing 91 osteotomies) who underwent segmental midshaft shortening osteotomies with internal fixation between January 2009 and December 2013. Radiographs were reviewed to determine when union was achieved. Union was defined as the bridging of 2 or more cortices in the anteroposterior, lateral, and oblique radiographic views. Osteotomies were classified as delayed union if they were not healed at 3 months postoperatively and nonunions if they were not healed at 6 months postoperatively. Results: Overall, 27 of 91 osteotomies met our radiographic classification of union and were healed by 3 months (29.7%). Sixty-nine of the 91 osteotomies healed by 6 months (75.8%) and were considered delayed unions. Twenty-two osteotomies were not healed yet and therefore were considered nonunions (24.2%). Of the 22 nonunions, 7 healed in an additional 2 months (8 months) for an overall healing percentage of 83.5%, (76 of 91). By 10 months, 6 more nonunions were healed (overall healing percentage of 90.1%, 82 of 91). Three additional nonunions went on to heal by 12.9 months, yielding a final union rate of 93.4% (85 of 91), while 6 were still considered nonunions (6.6%). Conclusion: We report that a significant percentage of segmental midshaft metatarsal shortening osteotomies experienced delayed unions and nonunions. These findings contrast those previously reported in the literature that metatarsal osteotomies have very low nonunion rates. These results support our hypothesis that these osteotomies require a prolonged amount of time to achieve bony healing and that they have a higher tendency to develop delayed and nonunions than previously reported. Level of Evidence: Level IV, retrospective case series.